2022
DOI: 10.3390/v14020388
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Orthopoxvirus Molecular Evolution

Abstract: Although variola virus (VARV) has been eradicated through widespread vaccination, other orthopoxviruses pathogenic for humans circulate in nature. Recently, new orthopoxviruses, including some able to infect humans, have been found and their complete genomes have been sequenced. Questions about the orthopoxvirus mutation rate and the emergence of new threats to humankind as a result of the evolution of circulating orthopoxviruses remain open. Based on contemporary data on ancient VARV DNA and DNA of new orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 45 publications
2
75
1
Order By: Relevance
“…MPXV belongs to the genus Orthopoxvirus , which also includes the smallpox virus (causing smallpox), vaccinia virus (used for the smallpox vaccine), and cowpox virus [36] . Monkeypox was first discovered in a Danish laboratory in 1958 [37] .…”
Section: Epidemiologymentioning
confidence: 99%
“…MPXV belongs to the genus Orthopoxvirus , which also includes the smallpox virus (causing smallpox), vaccinia virus (used for the smallpox vaccine), and cowpox virus [36] . Monkeypox was first discovered in a Danish laboratory in 1958 [37] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Ferrari et al estimated the evolutionary ratio as 8.5 × 10 −6 substitutions/site/year using Lithuanian samples, and Ferrari et al estimated it as 1.067 × 10 −5 substitutions/site/year using Lithuanian, Czech, and British samples [155,159]. However, ancient VARV was sequenced using older samples of Northern European specimens approximately 970 to 1400 years old, indicating that the MRCA of VARV was ~1700 years ago, and the accumulation rate of nucleotide substitutions was 3.7 × 10 −6 to 6.5 × 10 −6 substitutions/site/year [66,160]. These estimation results differed from the ratio estimated from time-structured samples, 1 × 10 −5 substitutions/site/year, isolated in the 20th century [170].…”
Section: Specific Ancient Viral Studies Inferring Past Pandemic and E...mentioning
confidence: 99%
“…It was suggested that the orthopoxvirus species originated from a common ancestor containing all genes present in current orthopoxviruses and that the long-term adaptation within host species caused the reduction in active genes. Babkin also revealed the differences in terms of gene contents between ancient VARV and its modern equivalent and suggested that the ancestral species contained all of the genes present in orthopoxviruses today and that long-term adaptation to within-host species occurred through a reduction of active genes [160].…”
Section: Specific Ancient Viral Studies Inferring Past Pandemic and E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Monkeypox virus (MPXV) is a zoonotic orthopoxvirus endemic in Central and West Africa 5,6 . Since May 2022, thousands of cases of MPXV have been reported in 50 non-endemic countries worldwide, with sustained human-to-human transmission 7 .…”
Section: Introductionmentioning
confidence: 99%